Management of Narcotics Recidivist Prisoners - Adi Putra (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Repetition of criminal acts or recidivists is a familiar phenomenon in Indonesia, especially acts of narcotics user recidivate, many factors cause a person to repeat his crime, such as economic interests, limited employment, low levels of education is a common problem someone takes a shortcut to get economic success. Correctional Institutions are expected to be able to become a place to return prisoners to become members of the community that are useful for themselves family and also the community but the reality is not as expected. The problem that will be discussed in the writing of this journal is to analyze the factors and how to deal with narcotics addicts so that they do not repeat their actions. Writing this journal uses qualitative methods and data obtained from Literature studies and Document studies. Based on the results of the Analysis of Literature studies and Document studies as well as previous research and discussion by the author emphasizes that the criminal process is said to fail when others commit the same and recurring crimes, and the factors that influence a person to become a narcotics addict to become recidivism are internal and external factors